Plane Shock Waves in Monoatomic Gas. Comparison Between Experimental and Theoretical Results. - Fiszdon, W.; Herczyński, R.; Walenta, Z. (Engineering Transactions, 1976)
A review of the reeent theoretical and experimental results on the structure of the shock waves in monoatomic gas is presented. It follows from this review, that the research in this field has reached a very high level of perfection. However there are still some questions unanswered and further research is necessary mainly because understanding of the shock-wave structure can give deeper insight into the fundamentals of gas dynamics.